Residence Hall Experiences of International Students - Tambornino, Kim (My University, 2010)
Living in residence halls is a crucial part of the American college experience. The time spent in the residence halls is equally important to internation students studying in the U.S. This study surveyed the international students at the University of Wisconsin--Eau Claire to better understand their residence hall life experience.
Residence Life Experiences of International Students at UW-Eau Claire
Color poster with text, images, and table.
Keywords: University of Wisconsin--Eau Claire--Students--Conduct of life; Dormitories--Social aspects--Wisconsin--Eau Claire; Students, Foreign--Wisconsin--Eau Claire--Conduct of life; College students--Wisconsin--Eau Claire--Conduct of life; Posters